Mengembangkan Kreativitas Anak Usia Dini Dan Pendidikan Kesehatan Perilaku Hidup Bersih Sehat (PHBS) Di TK GMIM Hosana Pineleng - Sri Atikah; Ria Angelina Jessica Rotinsulu; Yoram Andhika Imanuel; Dahlia Mangantar (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Creativity if poorly developed from an early age can adversely affect future life. A child who cannot develop his creativity will lose confidence in him in the future because he feels in him there is nothing to be encouraged about. Promoting a child's creativity requires stimulus using a teaching strategy or method. The need for creativity to be developed at an early age is because at this age the child-children have the ability to respond to everything from the outside quickly. In addition to clean and healthy living behaviors (PHBS) in the school ward are conscious efforts of students and teachers to prevent disease, freeing a healthy environment from illness. The stages of brain development in preteens occupy the fastest possible position of up to 80% of brain development. The goal of devotion is to foster creativity and deliver health education in children of an early age. Public service activities have been conducted in the temple of hosana pineng district of minahasa sulawesi north on April 26, 2022. The development of children's creativity and PHBS application, through education and simulations. Applying the method of playing "slime" was one of the educational forms of preserving optimum development or growth of children ata very early age through creative, interactive and integrated play that jugan "slime" was a tool the teacher could observe and observe. Learners are also taught to do simple things as a child's routine of daily activities as an effort to maintain good health (washing hands and brushing teeth).The result of this PKM activity on the development of early childhood creativity in the creativity attainment indicator is that 16 children have a high level of creativity that shows the results are beginning to grow (MB) and 4 children show the undeveloped results (bb). As for PHBS children-a very early age children were especially conscious when teaching them how to wash their hands and brush their teeth.